2022
DOI: 10.1097/gme.0000000000001899
|View full text |Cite
|
Sign up to set email alerts
|

Management of cardiovascular disease in women with premature ovarian insufficiency: critical quality appraisal of clinical guidelines and algorithm development

Abstract: Objectives: 1) To assess the methodological quality of clinical practice guidelines (CPGs) associated with cardiovascular disease (CVD) in women with premature ovarian insufficiency (POI); 2) to formulate an algorithm to foster the implementation of guidelines by clinicians.Methods: A systematic search for CPGs in English and Chinese languages published between 2015 and 2020 was conducted. Assessment was conducted by two reviewers respectively via the Appraisal of Guidelines for Research and Evaluation II inst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(14 citation statements)
references
References 47 publications
1
10
0
Order By: Relevance
“…Unfortunately, we did not find any recommendations related to nursing diagnosis from the CPGs, which is consistent with the findings of previous studies. 9 19 The results suggested that nurses need to take PSD itself or nursing diagnoses related to PSD (eg, grieving, powerlessness, chronic sorrow, etc) as a diagnostic result, as this may lack accuracy and specificity for nursing diagnosis. Nursing diagnoses are clinical judgements about current or potential reactions to the health problems of individuals, families or communities.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Unfortunately, we did not find any recommendations related to nursing diagnosis from the CPGs, which is consistent with the findings of previous studies. 9 19 The results suggested that nurses need to take PSD itself or nursing diagnoses related to PSD (eg, grieving, powerlessness, chronic sorrow, etc) as a diagnostic result, as this may lack accuracy and specificity for nursing diagnosis. Nursing diagnoses are clinical judgements about current or potential reactions to the health problems of individuals, families or communities.…”
Section: Discussionmentioning
confidence: 99%
“…The decisions ought to be made by the authors and guided by the context. After reviewing the literature,18 19 the overall quality and recommendation of CPGs were both divided into three levels. The authors considered a CPG with values >60% in five or six domains as high quality, that with values >60% in three or four domains as average quality and that with values >60% in one or two domains as low quality.…”
Section: Methodsmentioning
confidence: 99%
“…Causes of induced premature menopause include chemotherapy and surgical procedure (i.e., bilateral oophorectomy). The importance of premature menopause is being emphasized as it is associated with an increased risk of MetS, cardiovascular disease (CVD), non-alcoholic liver disease (NAFLD)/metabolic associated fatty liver disease (MFFLD), stroke, osteoporosis, and premature death [ 24 , 25 ].…”
Section: Definition Of Menopause and Metabolic Disordersmentioning
confidence: 99%
“…Premature ovarian insufficiency (POI) refers to the exhaustion of ovarian reproductive and endocrine function before the age of 40 [ 1 ]. In POI, the most common symptoms are menstrual disturbance (amenorrhea or oligomenorrhea), hypoestrogenism, and infertility, and the most serious consequence is the conspicuously increased risk of cardiovascular diseases [ 2 ], osteoporosis [ 3 ], neurodegenerative disease [ 4 ], and type 2 diabetes mellitus [ 5 ], which are attributed to the lack of the protective effects of oestrogen. Although multiple factors, including genetic mutations, immune dysfunction, and iatrogenic factors such as chemotherapy, radiotherapy and ovarian surgery, have been reported to contribute to POI, the causes of most cases are still unclear [ 6 ].…”
Section: Introductionmentioning
confidence: 99%